Rhyolites of the Kiliya-Zmeinyi uplift on the Black Sea shelf: geochemical evidence of a non-subduction boundary between the East European Platform and the Scythian Plate - Shnyukova, K.Ye. (Geofizicheskiy Zhurnal, 2021)
The geochemistry of rhyolites uncovered at shallow depth by a borehole on the Kiliya-Zmeinyi uplift of the Black Sea northwestern shelf northeast of Zmeinyi island, in the junction zone of the East European platform and the Scythian plate, has been studied for the first time. This zone is considered by many geologists and geophysicists as a Late Paleozoic collisional suture that had been formed due to subduction of oceanic crust of the ocean, which adjoined the East European platform from the south, under the Scythian plate; it is traced from Dobrudzha to the Caspian Sea and named North Crimean. To check the subduction nature of the boundary between the East European platform and the Scythian plate, igneous rocks’ geochemical characteristics beeng indicators of various geodynamic regimes were used. A petrogeochemical comparison of rhyolites from the borehole in Zmeinyi area with acid igneous rocks known nearby has been carried out, namely with: 1) Late Permian subalkaline granites and rhyolites Turcoaia of the Macin zone of Northern Dobruja; 2) Triassic and / or Triassic-Jurassic trachyrhyolites and rhyolites of the Tulcea zone of Northern Dobruja and the Tatarbunar complex of the Pre-Dobruja depression. Some acid rocks of various ages and genesis from the southernmost margin of the Scythian plate (southwestern Crimea on- and offshore) were taken additionally for comparison. According to the distribution of rare earth elements, the position on the discriminant geochemical diagrams and the shape of curves on the multicomponent spider diagrams, the rhyolites of the Kiliya-Zmeinyi uplift exhibit not subduction but intraplate geochemical features closest to those of granites and rhyolites Turcoaia of the Macin zone of Northern Dobruja. Considering that the latter are reputed to be Late Permian, one can assume the same age for the rhyolites from the borehole in Zmeinyi area. Taking into account section features, geophysical information and geochemical similarity of magmatism, Kiliya-Zmeinyi uplift of the northwestern shelf seems to be a continuation of the Northern Dobruja structure into the Black Sea; it was a part of the hypothetical Late Paleozoic Euxinian orogen near its northern boundary. An absence of subduction geochemical properties in the studied presumably Late Permian rhyolites indicates that the junction zone of the East European platform and the Scythian plate in the Ukrainian shelf area is not a Late Paleozoic suture, but rather represents a thrust of the Euxinian orogen.